2000
DOI: 10.1073/pnas.98.1.37
|View full text |Cite
|
Sign up to set email alerts
|

2-Aminopurine fluorescence quenching and lifetimes: Role of base stacking

Abstract: 2-Aminopurine (2AP) is a fluorescent analog of guanosine and adenosine and has been used to probe nucleic acid structure and dynamics. Its spectral features in nucleic acids have been interpreted phenomenologically, in the absence of a rigorous electronic description of the context-dependence of 2AP fluorescence. Now, by using time-dependent density functional theory, we describe the excited-state properties of 2AP in a B-form dinucleotide stacked with guanosine, adenosine, cytosine, or thymine. Calculations p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
209
3
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 335 publications
(218 citation statements)
references
References 23 publications
5
209
3
1
Order By: Relevance
“…As shown in Figure 3, left panel, 2AP fluorescence intensity at position P7 increases with temperature from 4°C-35°C. These data are consistent with a structural model in which the stacking of P7 is disrupted at higher temperatures; quenching of its fluorescence due to formation of an electronic "supermolecule" state (Jean and Hall 2001) is progressively diminished as the 2AP spends less of its time stacked. In contrast, 2AP fluorescence emission at P8 has its highest intensity at 4°C, and becomes progressively less with increasing temperature (Fig.…”
Section: Temperature Dependence Of Steady-state Fluorescencesupporting
confidence: 76%
See 2 more Smart Citations
“…As shown in Figure 3, left panel, 2AP fluorescence intensity at position P7 increases with temperature from 4°C-35°C. These data are consistent with a structural model in which the stacking of P7 is disrupted at higher temperatures; quenching of its fluorescence due to formation of an electronic "supermolecule" state (Jean and Hall 2001) is progressively diminished as the 2AP spends less of its time stacked. In contrast, 2AP fluorescence emission at P8 has its highest intensity at 4°C, and becomes progressively less with increasing temperature (Fig.…”
Section: Temperature Dependence Of Steady-state Fluorescencesupporting
confidence: 76%
“…The sum of the amplitudes equals the apparent r 0 anisotropy value, which here varies from 0.29 to 0.33; the theoretical maximum value of r 0 for free 2AP is 0.4. Larsen et al (2001) attribute similar r 0 values observed in 2AP-DNA experiments to solvent relaxation, but based on electronic structure calculations (Jean andHall 2001, 2002), interactions with other bases could lead to very rapid depolarization that lower the apparent initial value.…”
Section: Time-resolved Fluorescence Anisotropymentioning
confidence: 94%
See 1 more Smart Citation
“…Studies have shown that aromatic stacking of AP with other bases gives rise to static quenching of fluorescence and that base collisions give rise to dynamic fluorescence quenching (28,29). Static quenching is sensitive to the local equilibrium structure of a DNA and may arise due to reversible formation of a ground-state binary complex between the fluorophore and the quencher.…”
Section: Discussionmentioning
confidence: 99%
“…Similar shifts in fluorescent maxima have been reported for PhIP (32) and benzo[a]pyrene (33) when these carcinogens are stacked with the bases at the lesion site. The shifts might be a result of universal (dipole-dipole relaxation) and/or specific (formation of H-bonds or other type of stacking) interactions in the excited state between the fluorophore and the neighboring group during fluorescence lifetime (28,34). A recent study involving quantum mechanical calculations of the (AP)T dinucleotide suggests that this shift arises from a perturbed excited-state electronic structure of AP resulting from a stacked conformation (28).…”
Section: Discussionmentioning
confidence: 99%